A report on the practice-in-industry training in fish culture - Estacio, Jose R. (Dilman, Quezon City College of Fisheries, University of the Philippines, 1950)
One of the principal and most dependable instruments of production of our fishery resources is the bangos fishpond. It was the mainstay of our fish supply even during the occupation as it had been dduring the pre-war days. Fish culture practices have alrady reached a high technical level. Fish culturists now are much more concerned than before with finding means to help nature in hastening not only reproduction but in speeding up the growth of fishes as well. They employ all the technical skills and knowledge available with the end in view of maintaining steady supply of fish with the lowest possible cost of production and in conserving the important natural food resources fo future use. Aside from the general fresh water species of crustaceans, mollusks and fish as dalag, hito and martiniko, the giant gouramay, which were imported from java, are now raised in controlled fresh water ponds. Oyster as food is as nutritious as eggs and milk. It plays a significant role in one's diet fior it contains proportionate amounts of calcium, phosphorus, iron, iodine and copper. Oyster is source of vitamins A, B, C and D. Oyster meat either fresh or preserved is in great ddemand. Oyster shells are sold for the manufacture of lime and calcium feed of animals, and for clutching purposes. The bureau of fisheries has at present one-hectare oyster demonstration farm at Bacoor bay, Cavite, where oysters are grown by the stake, hanging and long line methods.
Keywords: Fish-culture.